Isolation and screening of cellulolytic fungi from Salacca zalacca leaf litter - SITI LUSI ARUM SARI; RATNA SETYANINGSIH; NOVITA FITRIATUL AINI WIBOWO (Biodiversitas Journal of Biological Diversity, 2017)
Sari SLA, Setyaningsih R, Wibowo NFA. 2017. Isolation and screening of cellulolytic fungi from Salacca zalacca leaf litter. Biodiversitas 18: 1282-1288. Cellulases are the main enzymes in a bioconversion of lignocellulosic biomass. Fungal cellulases have been proven to be better candidates for this process than other microbial cellulases since they secrete free cellulase complex including endoglucanases, cellobiohydrolases, and Î²-glucosidase. This study was conducted to isolate and screen of cellulolytic fungi from Salacca leaf litter. There were about 12 fungal isolates which were obtained in this research and 8 isolates showed cellulolytic activity. Based on morphological characters, these cellulolytic fungi were identified as belonging to 4 genera, i.e. Penicillium, Aspergillus, Paecilomyces, and Thielaviopsis. Based on clear zone formation, isolate SLL03, SLL06 and SLL10 showed highest cellulolytic activity. Whereas, based on 18S rRNA gene sequence, these isolates were identified as Aspergillums flavus (SLL03), Penicillium sp. (SLL06) Thielaviopsis ethacetica (SLL10). Therefore, these isolates would be good candidates for cellulase producer.